Application of Dynamic Replacement in a Steel Pipe Factory - Hamidi, Babak; Nikraz, Hamid; Varaksin, S. (Australian Geomechanics Society, 2011)
Prior to the construction of Al Jazira Steel Pipe Factory (AJSPF), almost all buildings in the Industrial City of Abu Dhabi were constructed on piles. This was due to the presence of compressible layers of soil, especially a superficial layer composed of one to four metres of soft sandy silts and clays. To the knowledge of the authors AJSPF is the first project in this area that has been built without the implementation of any piles and founded on shallow foundations improved by Dynamic Replacement. Variations of loading conditions and design criteria has made this pioneer project of special interest. While classical Dynamic Replacement was used for some ground slabs, pre-excavated Dynamic Replacement was applied under single footings and heavily loaded storage areas. As a cost saving method, sand from local Abu Dhabi excavations was used as granular material in lieu of the more commonly used crushed stone. Pressuremeter Tests (PMT) and finite element analysis was able to demonstrate that acceptance was achieved.